Temporality of body mass index, blood tests, comorbidities and medication use as early markers for pancreatic ductal adenocarcinoma (PDAC): a nested case–control study - Tan, PS; Garriga, C; Clift, A; Liao, W; Patone, M; Coupland, C; Bashford-Rogers, R; Sivakumar, S; Hippisley-Cox, J (BMJ Publishing, 2022)
Objective Prior studies identified clinical factors associated with increased risk of pancreatic ductal adenocarcinoma (PDAC). However, little is known regarding their time-varying nature, which could inform earlier diagnosis. This study assessed temporality of body mass index (BMI), blood-based markers, comorbidities and medication use with PDAC risk .